ANALISIS KELEMBAGAAN BADAN STANDARDISASI INSTRUMEN LINGKUNGAN HIDUP DAN KEHUTANAN: SEBUAH KENISCAYAAN - Subarudi Subarudi (Jurnal Analisis Kebijakan Kehutanan, 2023)
The  Agency  for  Standardization  of  Environment  and  Forestry  Instruments-ASEFI  (Badan  Standardisasi Instrumen Lingkungan Hidup dan Kehutanan-BSILHK) as a planner, formulator, and implementor of environment and  forestry  is  still  facing  handicaps  in  implementing  its  tasks  and  function.  This  needs  an  institutional  analysis in  an  effort  to  solve  its  problems..This  research  aims  to  analyze  the  institutional  aspect  of  ASEFI  focusing  on regulation, organization structure and working mechanism, human resources and financial support. The research  approach used is a content analysis and descriptive qualitative methods. Research results revealed that policy and regulation that support the implementation of the task and function of ASEFI is relatively adequate and can be a guide in its operational pattern. The nomenclature of ASEFI and its technical implementation unit is still needed for further  improvement  and  its  working  mechanism  must  be  enhanced  both  inside  and  outside  of  the  Ministry of Environment and Forestry.  Priority programs should be conducted in a short-term period in the fulfillment of standardization analyst both in quality and quantity sides. Besides that, the legal financial source of ASEFI has not clear yet, so that it should be determined with its exact financial sources. There are six important steps to be done by ASEFI for improving its main tasks so that its performance could be improved significantly in the near future.